The city school resource pack communication, language and literacy term 1 kindergarten (The City School Lahore, 2022)
The City School's resource pack for Communication, Language, and Literacy provides engaging activities to enhance vocabulary, listening, speaking, and early reading and writing skills. It focuses on interactive, play-based learning to foster a love for language in young children. The materials support essential communication skills development in a fun and effective manner.